Power system linear modeling : Application for small signal stability analysis - Biteznik, Carlos Ezequiel (2013)
This paper presents the calculation of the state matrix A of the power system through a program developed under MATLAB. This program is called SIAM (Sistema Informático para Análisis Modal - Computational System for Modal Analysis). The state matrix is obtained from the load flow solution data and from the dynamic model parameters employed. The detailed models of synchronous machines, automatic voltage regulators and power system stabilizers are linearized for the calculation. To evaluate the method proposed, there is a comparison of results between SIAM and a commercial program for a reference case published.